Nonhomologous DNA end joining and chromosome aberrations in human embryonic lung fibroblasts treated with environmental pollutants - Rossner, Pavel; Rossnerova, Andrea; Beskid, Olena; Tabashidze, Nana; Libalova, Helena; Uhlirova, Katerina; Topinka, Jan; Sram, Radim J (Mutation research, 2014)
In order to evaluate the ability of a representative polycyclic aromatic hydrocarbon (PAH) and PAH-containing complex mixtures to induce double strand DNA breaks (DSBs) and repair of damaged DNA in human embryonic lung fibroblasts (HEL12469 cells), we investigated the effect of benzo[a]pyrene (B[a]P) and extractable organic matter (EOM) from ambient air particles <2.5μm (PM2.5) on nonhomologous DNA end joining (NHEJ) and induction of stable chromosome aberrations (CAs). PM2.5 was collected in winter and summer 2011 in two Czech cities differing in levels and sources of air pollutants. The cells were treated for 24h with the following concentrations of tested chemicals: B[a]P: 1μM, 10μM, 25μM; EOMs: 1μg/ml, 10μg/ml, 25μg/ml. We tested several endpoints representing key steps leading from DSBs to the formation of CAs including histone H2AX phosphorylation, levels of proteins Ku70, Ku80 and XRCC4 participating in NHEJ, in vitro ligation activity of nuclear extracts of the HEL12469 cells and the frequency of stable CAs assessed by whole chromosome painting of chromosomes 1, 2, 4, 5, 7 and 17 using fluorescence in situ hybridization. Our results show that 25μM of B[a]P and most of the tested doses of EOMs induced DSBs as indicated by H2AX phosphorylation. DNA damage was accompanied by induction of XRCC4 expression and an increased frequency of CAs. Translocations most frequently affected chromosome 7. We observed only a weak induction of Ku70/80 expression as well as ligation activity of nuclear extracts. In summary, our data suggest the induction of DSBs and NHEJ after treatment of human embryonic lung fibroblasts with B[a]P and complex mixtures containing PAHs.
Keywords: histony; lidské chromozomy; Cell Line; embryo savčí; fibroblasty; Particulate Matter; pevné částice; Fibroblasts; plíce; fosforylace; Česká republika; látky znečišťující životní prostředí; benzopyren; Benzo[a]pyrene; Chromosome aberrations; Phosphorylation; Embryo, Mammalian; antigeny jaderné; translokace genetická; DNA vazebné proteiny; Urban Renewal; Extractable organic matter; Benzo(a)pyrene; antigen Ku; Czech Republic; oprava DNA spojením konců; Antigens, Nuclear; Lung; DNA End-Joining Repair; lidé; obnova měst; Double-strand DNA breaks; Humans; Ku Autoantigen; Translocation, Genetic; buněčné linie; Environmental Pollutants; Histones; Chromosomes, Human; DNA-Binding Proteins; Nonhomologous DNA end joining repair